Flavonoids in Decorticated Sorghum Grains Exert Antioxidant, Antidiabetic and Antiobesity Activities - Ofosu, Fred Kwame (Molecules, 2020)
Eight new genotypes of brown sorghum grain were decorticated and assessed for their antioxidant, antidiabetic and antiobesity activities in vitro. The DPPH and ABTS radical scavenging assays of the soluble fractions were evaluated, followed by digestive enzymes and advanced glycation end-products (AGEs) formation inhibition assays. DSOR 33 and DSOR 11 exhibited the highest DPPH (IC(50) = 236.0 ± 1.98 µg/mL and 292.05 ± 2.19 µg/mL, respectively) and ABTS radical scavenging activity (IC(50) = 302.50 ± 1.84 µg/mL and 317.05 ± 1.06 µg/mL, respectively). DSOR 17, DSOR 11 and DSOR 33 showed significantly higher inhibitory activity of both α-glucosidase and α-amylase (IC(50) = 31.86, 35.10 and 49.40 µg/mL; and 15.87, 22.79 and 37.66 µg/mL, respectively) compared to acarbose (IC(50) = 59.34 and 27.73 µg/mL, respectively). Similarly, DSOR 33, DSOR 11 and DSOR 17 showed potent inhibition of both AGEs and lipase with IC(50) values of 18.25, 19.03 and 38.70 µg/mL; and 5.01, 5.09 and 4.94 µg/mL, respectively, compared to aminoguanidine (52.30 µg/mL) and orlistat (5.82 µg/mL). Flavonoids were the predominant compounds identified, with flavones being the major subclass in these three extracts. Our findings suggest that decorticated sorghum grains contain substantial amounts of flavonoids and could be promising candidates for the prevention and treatment of diabetes and obesity.